Identification and Splicing Characterization of Novel TMC6 and TMC8 Variants Associated With Epidermodysplasia Verruciformis in Three Chinese Families - Wang, Rongrong; Liu, Jiawei; Yang, Xueting; Habulieti, Xiaerbati; Yu, Xue; Sun, Liwei; Zhang, Han; Sun, Yang; Ma, Donglai; Zhang, Xue (Frontiers in Genetics, 2021)
Background Epidermodysplasia verruciformis (EV) is a rare genodermatosis characterized by abnormal susceptibility to human beta papillomavirus infections and a particular propensity to develop non-melanoma skin cancers. The majority of EV cases are caused by biallelic null variants in TMC6, TMC8 and CIB1. This study aimed to identify disease-causing variants in three Chinese families with EV and to elucidate their molecular pathogenesis. Methods Genomic DNA from the probands of three EV families was analyzed by whole exome sequencing (WES). cDNA sequencing was performed to investigate abnormal splicing of the variants. Quantitative RT-PCR (qRT-PCR) was conducted to quantify the mRNA expression of mutant TMC6 and TMC8. Results WES identified two novel homozygous variants (c.2278-2A>G in TMC6 and c.559G>A in TMC8) in family 1 and 2, respectively. In family 3, WES revealed a recurrent and a novel compound heterozygous variant, c.559G>A and c.1389G>A, in TMC8. The c.2278-2A>G TMC6 variant led to the skipping of exon 19 and resulted in premature termination at codon 776. Subsequent qRT-PCR revealed that the aberrantly spliced transcript was partly degraded. Notably, the TMC8 c.559G>A variant created a novel acceptor splice site at c.561 and yielded three different aberrant transcripts. qRT-PCR revealed that most of the mutant transcripts were degraded via nonsense-mediated mRNA decay. Conclusions We identified three novel disease-causing variants in TMC6 or TMC8 in three Chinese families with EV. The EV phenotypes of the three patients were due to a reduction in TMC6 or TMC8. Our findings expand the genetic causes of EV in the Chinese population.